SENTIMEN ANALISIS PUBLIK TERHADAP VIRUS COVID-19 PADA MEDIA SOSIAL TWITTER MENGGUNAKAN METODE NAÏVE BAYES - Serafim Clara, (2021)
Twitter is a social media platform where people may directly share information, express opinions and criticism. Covid-19 is an epidemic that spreads so quickly that almost the whole world feels its impact. This immediately stirred the virtual world and become the number one trending on twitter. This opinion can be analyzed with sentiment analysis which grouped them into positive sentiment and negative sentiment, then using the Naïve Bayes classification algorithm. The data was taken on December 11, 2020 in 2 regions, namely DKI Jakarta and Surabaya using the API on Twitter and also the geolocation feature with #Covid-19. The results obtained that the data from the DKI Jakarta region has the highest accuracy value in sample 2, with 78%, while the data from the Surabaya region has the highest accuracy value in sample 1 with 83%.